CXCR4 and CXCL12 Expression in Rectal Tumors of Stage IV Patients Before and After Local Radiotherapy and Systemic Neoadjuvant Treatment - Tamas, Karin; M. Domanska, Urszula; H. van Dijk, Tonnis; Timmer-Bosscha, Hetty; Havenga, Klaas; Karrenbeld, Arend; J. Sluiter, Wim; C. Beukema, Jannet; A.T.M. van Vugt, Marcel; G.E. de Vries, Elisabeth; A.P. Hospers, Geke; M.E. Walenkamp, Annemiek (Current Pharmaceutical Design, 2015)
Metastatic rectal cancer patients could benefit from novel therapeutic approaches. The signaling network formed by chemokines and their receptors can promote metastasis and resistance to current anticancer treatments. This study assessed the expression of chemokine receptor 4 (CXCR4) and its ligand CXCL12 immuhistochemically in stage IV rectal tumors. Paraffin-embedded primary tumor collected before and after local radiotherapy and systemic treatment with bevacizumab, oxaliplatin and capecitabine was analyzed. Receptor and ligand expression was assessed in the cytoplasm and nucleus of tumor, stromal and normal rectal crypt cells. Baseline expression of CXCR4 and CXCL12 was correlated with patients' pathologic response to treatment. At diagnosis (n=46), 89% of the rectal tumors expressed cytoplasmic CXCR4 and 81% CXCL12. Nuclear CXCR4 expression in tumor cells was present in 30% and nuclear CXCL12 expression in 35% of the tumors. After radiochemotherapy and administration of bevacizumab, nuclear CXCL12 expression was observed in 79% of residual tumors, as compared to 31% of the paired tumor samples expressing nuclear CXCL12 before treatment (P=0.001). There were no differences in CXCR4 or CXCL12 expression at baseline between the patients who had (n=9) and did not have (n=30) a pathologic complete response. Our results show that CXCR4 and CXCL12 are extensively expressed in primary rectal tumors of patients presenting with metastatic disease, while radiochemotherapy and bevacizumab further upregulate CXCL12 expression. These data indicate the importance of the CXCR4/CXCL12 axis in rectal tumor biology, and may suggest the CXCR4/CXCL12 receptor-ligand pair as a potential therapeutic target in metastatic rectal cancer.
Keywords: bevacizumab